Influence of the local anesthetic tetracaine on the phase behavior and the thermodynamic properties of phospholipid bilayers. - Böttner, M (1993)
We investigated the influence of the local anesthetic tetracaine on the thermodynamic properties and the temperature- and pressure-dependent phase behavior of the model biomembrane 1,2-dimyristoyl-sn-glycero-3-phosphocholine by using volumetric measurements at temperatures ranging from 0 degrees to 40 degrees C and at pressures from ambient up to 1000 bar. The pVT measurements were complemented by temperature-dependent differential scanning calorimetric measurements. Information about the influence of different concentrations of the local anesthetic on the thermodynamic changes accompanying the lipid phase transitions, and on the thermal expansion coefficient, the isothermal compressibility, and the volume fluctuations of the lipids in their different phases, could be obtained from these experiments. The incorporation of tetracaine leads to an overall disordering of the membrane, as can be inferred from the depression of the main transition temperature and the reduction of the volume change at the main lipid phase transition. The expansion coefficient alpha p and the isothermal compressibility chi T of the lipid bilayer are enhanced by the addition of tetracaine and strongly enhanced values of alpha p and chi T, and the lipid volume fluctuations are found in the direct neighborhood of the main phase transition region. As tetracaine can be viewed as a model system for amphiphilic molecules, these results also provide insight into the general understanding of the physicochemical action of amphiphilic molecules on membranes. The experimental results are compared with recent theoretical predictions for the phase behavior of anesthetic-lipid systems, and the biological relevance of this study is discussed.